Aplicación foliar del aminoquelato CaBZn y tierra de diatomeas en la sanidad, rendimiento y rentabilidad del cacao CCN-51 - Muñoz Zambrano, Andy Daniel (2024)
The objective of this study was to evaluate the effectiveness of foliar application of CaBZn aminochelate and diatomaceous soil on the health, yield and profitability of CCN-51 cocoa. Factorial treatments of three levels of CaBZn aminochelate (1.0, 1.5 and 2.0 L ha-1) and two levels of diatomaceous soil (with and without application), and a control were evaluated. A randomized complete block design with seven treatments, three replicates and 21 experimental units were used. The main variables recorded were diseased cobs (DS), grain yield (GD) and economic profitability (ER). The data were analyzed with ANOVA and Tukey test (α = 5%). The combined application of CaBZn aminochelate with diatomaceous soil produced a decrease in DS of 33.57 and 50.97 % in relation to the foliar treatments of CaBZn aminochelate without diatomaceous soil and the control, respectively. The RG was increased by 18.73 and 36.50 % by the combined application of CaBZn aminochelate with diatomaceous soil, in contrast to the application of CaBZn aminochelate without diatomaceous soil and the control, in their respective order. All treatments with CaBZn aminochelate and diatomaceous soil achieved an ER greater than 300%, being the dose of 1 L ha-1 of CaBZn aminochelate mixed with diatomaceous soil, the treatment that achieved the highest ER. It is concluded that the foliar application of CaBZn aminochelate and diatomaceous soil was effective in enhancing the yield and profitability of CCN-51 cocoa.